Association between controlling nutritional status score and the prognosis of patients with acute myocardial infarction: a systematic review and meta-analysis - Peng, Lei; Tang, Jian; Zhang, Ningjun; Zhang, Zhongnan; Wang, Deqi; He, Youfu (Frontiers in Nutrition, 2025)
BackgroundRecent studies have reported growing evidence supporting applying the controlling nutritional status (CONUT) score in acute myocardial infarction (AMI) patients. This investigation intended to ascertain the link between CONUT scores and the prognosis in the AMI population.MethodsMultiple electronic databases, encompassing PubMed, Web of Science, Embase, and the Cochrane Library, were retrieved from the inception of the databases until July 20, 2024, to explore the link between CONUT scores and adverse clinical outcomes in individuals with AMI. Primary outcomes consisted of major adverse cardiovascular events (MACE) and mortality, while secondary outcomes encompassed stroke, cardiac death, myocardial reinfarction, revascularization, ventricular arrhythmias, and atrioventricular block. A random-effects meta-analysis was executed, with CONUT scores treated as either categorical or continuous variables. Sensitivity analyses and Egger’s test were conducted to appraise the robustness of results and publication bias, respectively. Subgroup analyses were executed to account for various confounding factors. Moreover, the GRADE system was leveraged to appraise the quality of evidence for all outcomes.ResultsFifteen studies were included in our analysis. The statistical analyses on both categorical and continuous variables unraveled that a high CONUT score was markedly linked to an elevated risk of MACE [categorical variable: odds ratio (OR) = 1.75, 95% confidence interval (CI) = 1.42–2.15; continuous variable: standardized mean difference (SMD) = 1.02, 95% CI = 0.78–1.26], mortality (categorical variable: OR = 2.08, 95% CI = 1.70–2.55; continuous variable: SMD = 1.16, 95% CI = 0.57–1.74), cardiac death (categorical variable: OR = 2.81, 95% CI = 1.67–4.73), myocardial reinfarction (categorical variable: OR = 2.21, 95% CI = 1.28–3.83), and atrioventricular block (categorical variable: OR = 5.21, 95% CI = 1.83–14.89) in AMI patients. However, no significant association was found between a high CONUT score and stroke (categorical variable: OR = 1.52, 95% CI = 0.98–2.35), revascularization (categorical variable: OR = 2.92, 95% CI = 0.58–14.79), and ventricular arrhythmias (categorical variable: OR = 2.57, 95% CI = 0.06–107.21).ConclusionThe CONUT score may serve as a promising and cost-effective prognostic biomarker for individuals with AMI.Systematic review registrationPROSPERO: CRD42024574048.